Deixis used in the novel entitled the good muslim by tahmima anam - Siska Purwanti; Rusman Roni; Artanti Puspita Sari (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
his research investigated Deixis used in the novel entitled The Good Muslim by Tahmima Anam.This study was conducted to find out; (1) types of deixis contained in utterances of the novel entitled the Good Muslim by Tahmima Anam, (2) types of deixis were used most in the Novel entitled The Good Muslim by Tahmima Anam. Therefore, it gived significant to the author herself, the learners, other researchers and english teachers. The writer used levinson’s theory in analyzing the data. The methodology of this research was qualitative descriptive study. The technique used to collect the data was documentation. The data was taken from 1.972 utterances of the novel entitled the Good Muslim by Tahmima Anam. From the data have been analyzed, it was found that there were five types of deixis, they were person deixis occured 1.723 times (87.4%), place deixis occured 53 times (2.7%), time deixis occured 68 times (3.4%), discourse deixis occured 83 times (4.2 %), person deixis occured 45 times (2.3 %). The most commonly used types of deixis was person deixis occuring 1.723 times (87.4%).